ENHANCING READING AND COMPREHENSION SKILLS IN YOUNG LANGUAGE LEARNERS: METHODS AND ACTIVITIES (Multidisciplinary Journal of Science and Technology, 2024)
This article explores various effective methods and activities aimed at improving reading and comprehension skills in young language learners. The importance of developing these skills at an early age is highlighted, and the article provides insights into strategies such as interactive reading, vocabulary building exercises, and comprehension activities. The effectiveness of these methods in promoting language acquisition and literacy development is discussed, offering valuable guidance for educators and parents seeking to support young learners in their reading journey.